Quantitative Risk Analysis of Concrete Structures in Public Buildings Using Rebound Hammer and UPV Data - Haedar, Ahmad Wahidiyat (PINISI Discretion Review, 2025)
This study introduces a quantitative risk analysis framework designed to evaluate the structural reliability of reinforced concrete elements within public buildings. The framework integrates non-destructive testing (NDT), specifically utilizing the Rebound Hammer and Ultrasonic Pulse Velocity (UPV) methods. Crucially, this research addresses a recognized gap in existing structural risk literature, which frequently concentrates on deterministic strength assessments without establishing a link between material degradation indicators and probabilistic risk levels. Leveraging empirical data derived from a comprehensive inspection of a public building, the study applied a holistic evaluation encompassing material quality, probability of failure, and severity of consequences to determine the risk category for each structural component. The methodological approach involved NDT-based strength estimation, statistical probability calculation, and the formulation of a risk matrix to derive quantifiable risk scores. The key findings demonstrate that variations in concrete quality, as evidenced by rebound values and UPV velocities, exert a substantial influence on the probability of structural underperformance. Structural elements exhibiting lower NDT values were consistently correlated with elevated risk scores, thus affirming the critical relationship between material deterioration and safety risk. The integrated risk matrix successfully identified priority elements necessitating early intervention, thereby validating the method's effectiveness in supporting proactive maintenance decision-making. Overall, this research underscores the imperative of combining diagnostic data with probabilistic frameworks to refine risk-informed asset management in public infrastructure. The proposed approach offers a practical instrument for stakeholders seeking to enhance structural safety planning and optimize rehabilitation strategies.